Structural equation modeling (SEM) analysis based on UTAUT2 theory on e-commerce adoption - Widya Reza; Faradiba Jabnabillah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
E-commerce adoption with the UTAUT 2 model is a complex and multidimensional issue that connects multiple dimensions. A statistical method that can explain the relationship between one latent variable and another variable is Structural Equation Modeling (SEM). This study aims to create a structural model of e-commerce adoption using SEM based on indicators in the UTAUT2 theory. The data used in this study is primary data obtained through a survey of MSME actors in Batam City using a questionnaire with the purposive sampling method. The sample used was 200 MSMEs. The analysis results show that the value on the Behavioral Intention variable was 88.6%, and the Use Behavior variable was 76.8%. value of 97.4% indicates that the exogenous latent variable strongly affects the endogenous latent variable. The goodness of the fit value suggests that the SEM model in this study can explain empirical data or field data by 83%. The hypothesis testing results are that Behavioral intention significantly affects effort expectancy, facilitating condition, performance expectancy, and price value. Related to indirect effect, variables that affect user behavior through behavioral intention are significantly the variables of effort expectancy, facilitating condition, habit, performance expectancy, and price value.